The most beautiful libraries in the world - Laubier, Guillaume de. (Harry N. Abrams, 2003)
Here, for the first time, architectural photographer Guillaume de Laubier takes the reader on a privileged tour of twenty-three of the world's most historic libraries, representing twelve countries and ranging from the great national monuments to scholarly, religious, and private libraries: the baroque splendor of the Institut de France in Paris; the Renaissance treasure-trove of the Riccardiana Library in Florence; the majestic Royal Monastery in El Escorial, Spain; the hallowed halls of Oxford's Bodleian Library; and the New York Public Library, a Beaux-Arts masterpiece. Also included are the smaller abbey and monastic libraries - often overlooked on tourist itineraries - each containing its own equally important collections of religious and philosophical writings, manuscripts, and church history. Through color photography one can marvel at the grandeur of the great public libraries while relishing the rare glimpses inside scholars-only private archives